Bisphenol A and Metabolic Syndrome: Results from NHANES - Srinivas Teppala; Suresh Madhavan; Anoop Shankar (International Journal of Endocrinology)
Background. Bisphenol A (BPA) is detected in the urine of >95% of US adults. Recent evidence from population-based studies suggests that BPA is associated with individual components for metabolic syndrome (MetS). However, no previous study has examined the direct association between BPA and MetS. Methods. We examined 2,104 participants from the National Health and Nutrition Examination Survey 2003–2008. The main outcome was the presence of MetS (n=741). Results. Increasing levels of urinary BPA were positively associated with MetS, independent of confounders such as age, gender, race/ethnicity, smoking, alcohol intake, physical activity, and urinary creatinine. Compared to tertile 1 (referent), the multivariable adjusted odds ratio (95% confidence interval) of MetS in tertile 3 was 1.51 (1.07–2.12); P-trend was 0.02. Conclusions. Urinary BPA levels are positively associated with MetS, in a representative sample of US adults and independent of traditional risk factors for MetS. Future, prospective studies are needed to confirm our findings.